PEMANFAATAN RUANG TERBUKA PUBLIK SEBAGAI AKTIVITAS PEDAGANG KAKI LIMA STUDI KASUS DI KAWASAN ALOON ALOON KAUMAN, KOTA SEMARANG - Oktaviani, Yumna; Hari Wibisono, Bambang (Jurusan Teknik Perencanaan Wilayah dan Kota, Fakultas Sains dan Teknologi, Universitas Islam Negeri Alauddin Makassar, 2024)
The presence of street vendors (street vendors) in urban spaces is generally a problem, as they are known as the irregularity of the city and occupy public spaces which is not recommended. PKL is growing rapidly in various areas of the city, including the Aloon Aloon Kauman area which is also a residential, trade, cultural heritage, and cultural tourism area. The existence of Johar Market in the area is very important because it encourages street vendors to trade there. However, the growth of street vendors causes them to occupy every shoulder of the road in the area without paying attention to the location that should be intended for them such as sidewalks, road bodies, and shop fronts to become street vendors without paying attention to the surrounding activities, causing conflicts in space use and reducing the optimality of public spaces. This problem arises because the determination of the PKL activity space does not understand the characteristics of its activities and there is no clear reference in determining the PKL activity space. This highlights the importance of reviewing street vendor activity spaces and developing better policies to manage street vendors in urban spaces. The purpose of this study is to determine the behavior of street vendors in utilizing urban space related to their business activities. This study used quantitative methods with frequency distribution analysis techniques and cross-tabulation. From the research, it was found that street vendors in running their business use public space (sidewalks), because they utilize spaces that have a high level of visit intensity with agglomeration patterns grouped according to the type of merchandise.